The clinical efficacy and suitable implementation of two extracorporeal blood purification therapies: AN69-oXiris versus PMX-HP - Kim, Hye Sung; Chung, Yoon Ji; Lee, Gyeo Ra; Kim, Eun Young (Frontiers in Medicine, 2024)
Purpose In septic shock patients, pathogens and excessive endotoxins continuously overstimulate the host’s immune system with a cytokine storm that can lead to multi-organ failure and even mortality. Various types of extracorporeal blood purification treatments have recently been introduced to remove excessive endotoxins and cytokines. Herein, we compared the clinical efficacy of two blood purification methods, PMX-HP and AN69-oXiris, and discussed their detailed indications according to disease severity. Materials and methods From December 2016 to April 2023, patients who underwent emergent surgery due to septic shock secondary to peritonitis and subsequently received blood purification treatment with AN69-oXiris or PMX-HP were enrolled. Propensity score (PS)-matching was conducted to adjust for baseline characteristics between the two groups, and the changes in clinical parameters and outcomes were compared. Clinical outcomes were assessed in subgroups of patients who underwent PMX-HP treatment divided according to SOFA scores into low (0–7), intermediate (8–13), and high (> 13) disease severity groups. Results Forty patients received blood purification therapy with either PMX-HP or AN69-oXiris during the study period. After 1:2 PS matching, six patients in the AN69-oXiris group and 12 patients in the PMX-HP group were finally analyzed. Vasoactive-inotropic scores (VISs) decreased in both groups after 48 h of treatment compared to the baseline values, but the change in VISs was more pronounced in the PMX-HP group −57.6 [interquartile range (IQR) = −166.4 – (−10)] vs. -22.9 [IQR = −64–0], respectively, p = 0.041. Decreases in cardiovascular SOFA scores were significantly pronounced in the PMX-HP group [−1.5 (IQR = −4 – 0) vs. 0 (IQR = −1 – 1), respectively, p = 0.035]. The 7-day mortality rate was significantly lower than the predicted mortality rate in a subgroup analysis of patients treated with PMX-HP in both the low disease severity group and the intermediate disease severity group. Conclusion PMX-HP and AN69-oXiris could be therapeutic options for refractory septic shock patients with intra-abdominal origins, especially after the surgical elimination of the infectious sources. A tailored modality choice that takes into account patient characteristics, such as disease severity and cost burden, could optimize the efficacy of this strategy.